Physical activity level among undergraduate students in Terengganu, Malaysia using pedometer - Noor Aini, Mohd Yusoff; Aryati, Ahmad; Mohd Razif, Shahril; Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa; Karimah Fakhriah, Ismail; Lua, Pei Lin; Hafizan, Juahir; Sharmila, Ganeson; Roslee, Rajikan (2017)
Physical activity contributes positively to health but sedentary lifestyle has been identified as the one of the leading risk factor for chronic diseases. In Malaysia, 35.2% adults are physically inactive using International Physical Activity Questionnaire (IPAQ). A cross-sectional study was conducted to determine the physical activity level among 95 undergraduate students at UniSZA using pedometer. Subjects consented and completed socio-demographic details and their weight and height were measured. Each subject was supplied with a pedometer (Omron, Walking stye One 2.1 HJ-321-E) and instructed to wear it for a week and record steps per day from the pedometer each night before bed. Descriptive statistic, and independent T-test were carried out to analyse the data (IBM SPSS Version 22.0). Results showed that 66.4% of the subjects (n=63) were classified as sedentary according to pedometer determined physical activity. Males recorded 6030.0±2993.64 significantly more steps than female (3755.5 ±1432.33) per day. Subjects in the age group of 18-20 years old had the highest mean average steps count (4597.34 ± 1834.26) than the older age group of 21-24 years old (4182.13±2767.39) and ≥25 years old (2997.14±1352.59) per day. Although majority of the subjects were in normal category of BMI (57.8%), only 5.2% were classified as somewhat active (4.2%) and highly active (1.0%) using pedometer determined physical activity level. In conclusion, majority of our subjects were classified as having sedentary lifestyle using pedometer physical activity levels. This study also showed that male students were more active than female students.